2006
DOI: 10.1007/s11469-006-9046-4
|View full text |Cite
|
Sign up to set email alerts
|

Hazardous and Harmful Alcohol Consumption Among Non-Psychotic Psychiatric Clinic Attendees in Oman

Abstract: Although interest in substance abuse in psychiatric patients has received increasing attention, there is scant study of hazardous and harmful drinking patterns in Arab/Islamic societies where socio-cultural patterning imposes total abstinence on drinking. However recent globalization has eroded such prescription. An aim of this study is to examine the severity of harmful and hazardous drinking in Oman. From Omani nationals seeking psychiatric consultation, an assessment of alcohol dependence or hazardous or ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
23
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 51 publications
2
23
0
Order By: Relevance
“…The vast majority of studies conducted in this region collected information on alcohol and substance use from clinical populations and rarely from the general public. The populations consisted of patients attending general psychiatric clinics (e.g., Amin, Hamdi, & Ghubash, 1996; Zaidan et al, 2007) in addition to in‐patients at dedicated drug and alcohol dependency units (e.g., Abalkhail, 2001; Bilal, 1988) and incarcerated populations (Amir, 1994; Ghubash & El‐Rufaie, 1997). In contrast to Western literature, where a large amount of alcohol‐related research is conducted with university/college student populations, only 3% of the located studies in this region used tertiary‐education student samples (Al‐Subaie & Al‐Hajjaj, 1995; El‐Anzey & Abel Moneim, 2003).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The vast majority of studies conducted in this region collected information on alcohol and substance use from clinical populations and rarely from the general public. The populations consisted of patients attending general psychiatric clinics (e.g., Amin, Hamdi, & Ghubash, 1996; Zaidan et al, 2007) in addition to in‐patients at dedicated drug and alcohol dependency units (e.g., Abalkhail, 2001; Bilal, 1988) and incarcerated populations (Amir, 1994; Ghubash & El‐Rufaie, 1997). In contrast to Western literature, where a large amount of alcohol‐related research is conducted with university/college student populations, only 3% of the located studies in this region used tertiary‐education student samples (Al‐Subaie & Al‐Hajjaj, 1995; El‐Anzey & Abel Moneim, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…An early study conducted in Kuwait reported that the mean daily drinking in a sample of 100 alcohol‐dependent patients was 300 grams of ethanol a day (Bilal & El‐Islam, 1985)—an amount markedly higher than the corresponding British sample (Bilal, Kristof, & El‐Islam, 1987a). In a recent study conducted in Oman (Zaidan et al, 2007), 66% of the 56 patients interviewed consumed alcoholic beverages on more than four occasions a week. For these participants, typical drinking sessions consisted of more than six drinks, with almost 50% consuming this amount on a daily basis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations